The Need of Contemporary Linguistic Studies for Artificial Intelligence – Cognitive Linguistics as a Mode - arioua, imane; ghilous, salah (El Omda in Linguistics and Discourse Analysis, 2023)
The need for modern linguistics to keep abreast of modern developments and digitization has become necessary in the light of the transformations that have taken place in today's era, the emergence of modern technological means and the intersection of science and the formation of so-called cognitive sciences; Led to the emergence of contemporary tongue trends influenced by the results of artificial intelligence and digital development: As computational and cognitive linguistics, they were the product of cognitive science and their synergy with the development of artificial intelligence software, as the computer became a machine that mimics the human mind of: Storing information, programming to arrange, retrieve and process. Hence the research of the topic with the title of the President here is: The need for a contemporary lesson of artificial intelligence - customary linguistics - is a model, and we therefore raise the following problems: How did the linguistic lesson (computer linguistics, customary linguistics) benefit from modern developments and artificial intelligence under interactive studies? How did the lesson begged through his contemporary research course with the achievements of the adjacent knowledge fields?